Hubungan Pola Asuh dengan Tingkat Stres Menjelang Ujian Pada Anak Kelas 6 di SDN 2 Sumber Kencono Wongsorejo - Erik Toga; Roudlotun Nurul Laili; Muhammad Nashir (NAJ Nursing Applied Journal, 2024)
This study examines correlation between parenting styles and stress levels among 6th-grade students at SDN 2 Sumber Kencono Wongsorejo prior to examinations. The study employed quantitative methods and utilized questionnaires as the primary means of collecting data. The sample was 35 6th-grade students who were about to take the exam, selected through purposive sampling. The findings show a correlation between the parenting style parents applied and the stress level experienced by children before the exam (p-value = 0.002). Students who experience democratic parenting tend to have lower stress levels compared to students who are educated with authoritarian, neglectful, or permissive parenting styles. This study concludes that parenting style is vital in determining children's stress levels before exams. Democratic style can help children manage stress more effectively. The findings are expected to be a reference for parents and schools in developing strategies to help children face stress before the exam. Keywords: 6th Grade Elementary School Children, Exams, Parenting Style, Stress Levels.